Anonyme Lehmbauten Anatoliens - Peters, Eckhart W. (ERDKUNDE, 1977)
This paper considers the architecture typical of large parts of Anatolia. The adobe buildings in rural settlement areas are essentially characterised by what might be called vegetative building, i.e.a style the course of which cannot be ascertained in advance. The chief characteristic of such vegetative building is the very fact of permanent alteration of the buildings in both the horizontal and the vertical direction;this may be influenced by a number of physical or anthropogenic factors. The factors for these alterations are the outcome of the increasing size of families and the varying property status, as well as the impermanent nature of the building materials and the consequent need for special, careful maintenance work. In keeping with the local Anatolian circumstances it is therefore appropiratc to classify the anonymous architecture not in accordance with the frequently fortuitous building plan but in accordance with the various building methods (additive, agglu tinating, regulative) which lead to the different forms of basic plan.